Virtual Worlds - in Elementary School & College Classrooms - Leong, Peter; Asselstine, Shane (Lupa empresarial, 2016)
This paper presents case studies of an elementary school class and a graduate college course designed to provide students with the opportunity to explore the use of virtual worlds—primarily Minecraft and Second Life—for teaching and learning. Based on the findings, implications for the design of virtual world classes are provided.